Incu-Stream 1.0: An Open-Hardware Live-Cell Imaging System Based on Inverted Bright-Field Microscopy and Automated Mechanical Scanning for Real-Time and Long-Term Imaging of Microplates in Incubator - Gürkan, Koray; GÜRKAN, GÜRAY (My University, 2019)
Microplate (i.e. microwell plate) is a flat plate that has a specific number of wells to be used as small test tubes in cell-culture studies. In most of the low-budget mammalian cell study laboratories, highly skilled laboratory personnel should determine microscopic changes in microplate well media by taking the microplate outside the incubator and by imaging each well medium under a microscope, with the risk of contamination and reliability degrading. An alternative solution is to use an in-incubator operated live-cell imaging device, which, however, cannot be afforded by low-cost laboratories. In this paper, we present the design, realization, and test stages of a microplate compatible inverted bright-field microscope system that can be used in incubators. The developed system enables real-time and long-term in-incubator imaging of any user-selectable microplate type. The device can capture bright-field microscopic images by using a low-cost CMOS image sensor, an inverted varifocal CCTV lens and an array of light emitting diodes. In addition, by developed two-axial movement stage and image augmenting algorithms, the whole area of a user selectable well (e.g. area of a 6.5 mm diameter well in a 96-well plate) can be automatically imaged without using any other third party software. The long-term performance of the system is tested in incubators with human embryonic kidney and breast cancer cell lines.
Keywords: Open-Hardware; Bright-Field Microscopy; Live-Cell Imaging; Time-Lapse Imaging; Image Stitching